PERAN APARAT DESA DALAM PENYELENGGARAAN PEMILIHAN KEPALA DESA KAIDUNDU KECAMATAN BULAWA - Paneo, Ibrahim; Tilome, Apris Ara; Gintulangi, Sri Lestari; Kiayi, Zumair (STISIPOL Mujahidin Buol, 2024)
This research aims to determine the role of Kaidundu village officials in the process of implementing the village head election using qualitative methods with descriptive research. The results of the research show that the role of the Kaidundu village officials in the election of the Kaidundu village head has a significant impact on the village head election process. The attitudes, social values, and role of village officials in carrying out village head elctions in Kaidundu village show that (1) The majority of village officials show a positive attitude towards the village head election process, by showing commitment and active participation in supporting the process. However, there are variations in individual attitudes that can influence their consistency and effectiveness in carrying out their duties. (2) Social values such as honesty, justice and transparency play an important role in the views and actions of village officials during the village head election process. However, there are also other factors such as loyalty to certain groups or candidates that can influence the interpretation and application of these values. And (3) The behavior of village officials, including interactions with the community and candidates, use of village resources, and decision making, has direct implications for the integrity and success of the village head election process. Having behavior that is consistent with recognized social values can increase community trust in village officials.